2018
DOI: 10.1128/iai.00615-17
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome Subunits Are Required for CD8 + T Cell Function and Host Resistance to Brucella abortus Infection in Mice

Abstract: The immunoproteasome is a specific proteasome isoform composed of three subunits, termed β1i, β2i, and β5i. Its proteolytic activity enhances the quantity and quality of peptides to be presented by major histocompatibility complex class I (MHC-I) molecules to CD8 T cells. However, the role of the combined deficiency of the three immunoproteasome subunits in protective immunity against bacterial pathogens has not been investigated. In this study, we addressed the role of the immunoproteasome during infection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
(66 reference statements)
0
9
0
1
Order By: Relevance
“…Infection with Brucella abortus in TKO mice led to an increased bacterial burden. This was associated with an impaired MHC I presentation of CD11c + cells and a reduced percentage of both CD4 + and CD8 + IFNg producing T cells as well as fewer Granzyme B producing CD8 + T cells (37). Similarly, infection with the protozaon Trypanosoma cruzi in TKO mice resulted in reduced MHC I expression and altered CD8 + effector T cell function, in both quantity and quality as there were fewer overall CD8 + effector cells and fewer IFNg producers (36).…”
Section: Discussionmentioning
confidence: 98%
“…Infection with Brucella abortus in TKO mice led to an increased bacterial burden. This was associated with an impaired MHC I presentation of CD11c + cells and a reduced percentage of both CD4 + and CD8 + IFNg producing T cells as well as fewer Granzyme B producing CD8 + T cells (37). Similarly, infection with the protozaon Trypanosoma cruzi in TKO mice resulted in reduced MHC I expression and altered CD8 + effector T cell function, in both quantity and quality as there were fewer overall CD8 + effector cells and fewer IFNg producers (36).…”
Section: Discussionmentioning
confidence: 98%
“…The antigen peptide which combined with MHC class I, hydrolyzed by immunoproteasome, has stronger CTL activation effect than that in constitutive proteasome (41,47,48). Gabriela et al demonstrated a negatively impact on MHC-I surface expression and antigen presentation process in immunoproteasome triple knockout mice, and cytotoxic activity of CD8 + T cell showed a consequently reduced tendency (49). Nagayama et al suggested that Th1 235 and Th17 differentiation was inhibited by a selective inhibitor of immunoproteasome in the murine model (50).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report linking these proteins to human immune responses except for PMSA2 and COTL1. PMSA2 is a subunit of the immunoproteasome which is known to be able to enhance the repertoire of peptides presented by MHC-I molecules [ 41 ]. In line with this observation, an increase in PSME1 and PSME2 (Proteasome activator complex subunit 1 and 2) protein following AS03 adjuvanted H5N1 influenza vaccination was observed in monocytes at Day 3, predicting later seroprotection status (based on protective levels of HAI titter) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%